Financial Distress Analysis Using the Altman Z-Score Method at PT. Indofarma Tbk Period 2019 to 2022 - Al Mutasimbillah, Muhammad Rofi Ussan; Paramitha, Dyah Ayu (Universitas Nusantara PGRI Kediri, 2024)
Research objectives: This research aims to measure the level of financial distress and the potential for bankruptcy that may occur at PT. Indofarma Tbk. Design/Method/Approach: The research method applied is quantitative descriptive, using a population consisting of the financial statements of PT. Indofarma Tbk., accessed through the website www.idx.co.id, particularly in the form of financial reports from 2019 to 2022. The analysis technique employed is the Altman Z-Score method, utilizing five ratios: the ratio of working capital to total assets, the ratio of retained earnings to total assets, the ratio of earnings before interest and taxes to total assets, the ratio of equity book value to total debt book value, and the ratio of sales to total assets. Research Findings: The research results indicate that PT. Indofarma Tbk. is predicted to face financial distress and the risk of bankruptcy from 2019 to 2022. Z-Score values for those years below 1.8 indicate that PT. Indofarma Tbk. is estimated to experience bankruptcy or financial distress.